Upaya Meningkatkan Hasil Belajar Materi Bangun Ruang Sisi Lengkung Melalui Metode Penemuan Terbimbing Pada Siswa Kelas IX D SMP Negeri 1 Ngluwar Magelang Semester Genap Tahun Pelajaran 2021/2022 - Samodra, Bambang (Faculty Of Education, 2022)
The material of non-polyhedrons or curved-surface solids is closely contextual to everyday life so that the concept must be thoroughly mastered by the students. The discussions of curved-surface solids take many real examples, while what students receive in the classroom is theoretically conceptual. Therefore, by mastering the material of curved-surface solids, students can gain knowledge and skills that are applicable in everyday life. This classroom action research generally aims to improve the learning outcomes in mathematics subject for students of class IX D of SMP Negeri 1 Ngluwar, while this paper has the purpose (1) To describe the implementation of the guided discovery method in improving student learning outcomes (2) To describe the level of learning outcomes of curved-surface solids material (3) To describe the behavioral changes that accompany the improvement of learning outcomes. The research was carried out in 2 cycles. Cycle 1 was carried out in 2 meetings, while cycle 2 was carried out in 2 meetings. So in total there are 4 meetings. There are 4 stages in the implementation of both cycle 1 and cycle 2, namely planning, action, observation, and reflection. Learning outcomes data were taken from the evaluation at the end of cycle 1 and cycle 2, while the data on the students’ behavioral changes are taken from an observation sheet. Changes in students’ behavior show that they start to get focused on learning, actively engaged in question-and-answer session, develop habit in taking notes, independent, develop integrity when working on their own, develop politeness in speaking, respecting the opinions of others and grow in self-discipline in terms of submitting assignments and punctuality. The results showed that (1) The guided discovery method could improve student learning outcomes (2) The average learning outcomes of curved-surface solids material increased by 3 points (3) There were changes in behavior that accompanied the increase in curved-surface solids learning outcomes.